A new classification scheme of European cold-water coral habitats: implications for ecosystem-based management of the deep sea - Davies, J. S.; Guillaumont, Brigitte; Tempera, Fernando; Vertino, A.; Beuck, L.; Olafsdottir, S. H.; Smith, C. J.; Fossa, J. H.; van den Beld, Inge; Savini, A.; Rengstorf, A.; Bayle, Christophe; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2017)
International audience Cold-water coral (CWC) habitats can form complex structures which provide refuge, nursery grounds and physical support for a diversity of other living organisms, but despite their ecological significance, CWCs are still vulnerable to human pressures such as fishing, pollution, ocean acidification and global warmingProviding coherent and representative conservation of vulnerable marine ecosystems including CWCs is one of the aims of the Marine Protected Areas networks being implemented across European seas and oceans under the EC Habitats Directive, the Marine Strategy Framework Directive and the OSPAR Convention. In order to adequately represent ecosystem diversity these initiatives require a standardised habitat classification that organises the variety of biological assemblages and provides consistent and functional criteria to map them across European Seas (Howell 2010). One such classification system, EUNIS, enables a broad level classification of the deep sea based on abiotic and geomorphological features. More detailed lower biotope-related levels are currently under-developed, particularly with regards deep-water habitats (>200 m depth).This paper proposes a hierarchical CWC biotope classification scheme that could be incorporated by existing classification schemes such as EUNIS. The scheme was developed within the EU FP7 project CoralFISH to capture the variability of CWC habitats identified using a wealth of seafloor imagery datasets from across European seas and oceans. Depending on the resolution of the imagery being interpreted, this hierarchical scheme allows data to be recorded from broad CWC biotope categories down to detailed taxonomy-based levels, thereby providing a flexible yet valuable information level for management. The CWC biotope classification scheme identifies 81 biotopes and highlights the limitations of the classification framework and guidance provided by EUNIS, the EC Habitats Directive, OSPAR and FAO; with limited categories for identifying and ...